The effect of lime (Citrus Aurantifola Swingle) peel extract in periodontal dressings on the number of fibroblasts in the gingival wound healing process - Malianawati Fauzia; Audia Putri Dewanti (Dental Journal (Majalah Kedokteran Gigi), 2022)
Background: Periodontal dressing commonly used in dentistry today does not contain compounds that can accelerate wound healing. Lime (Citrus aurantifolia Swingle) peel contains flavonoids that play a role in increasing fibroblast cells so that they can accelerate the healing process. Periodontal dressings supplemented with lime (Citrus aurantifolia Swingle) peel extract are expected to provide an alternative material that can accelerate wound healing in addition to closure. Purpose: The study aims to determine the effect of adding lime (Citrus aurantifolia Swingle) peel extract to periodontal dressings on the increase in the number of fibroblasts in the gingival healing process. Methods: The study was conducted in an experimental laboratory in vivo. The study used a post-randomised control group of 32 rabbits with lesions of the mandibular gingiva using a 2 mm diameter punch biopsy. The experimental animals were divided into 8 groups, namely the control group, which was treated with periodontal dressings without the addition of lime (Citrus aurantifolia Swingle) peel extract, and the treatment group, which was treated with periodontal dressings with the addition of the extract. Histological observations of the tissues were performed with HE staining to count the number of fibroblasts. Results: Statistical test results showed that there was a significant difference in the number of fibroblasts between the control group and the treatment group on day 3 and day 5 (ANOVA, p <0.05). Conclusion: Adding extra lime (Citrus aurantifolia Swingle) peel to the periodontal dressing increases the number of fibroblast cells after gum injury.